Prevalence of vision impairment in Rwanda: a hospital-based study - Ayobi, Benedict; Hansraj, Rekha; Rampersad, Nishanee; Urimubenshi, Gerard (Frontiers in Medicine, 2025)
BackgroundVision impairment (VI) is a global health challenge with its impact cutting across ages, gender, and all domains of life. A shift in global demographics due to increasing life expectancy is expected to increase the burden of VI.AimThis study sought to determine the prevalence of VI in the general population among selected public hospitals in Kigali and southern Rwanda.MethodsThis retrospective hospital-based study used five public hospitals from Kigali and Southern Rwanda. Patient files from 1st January 2018 to 31st December 2023 were sampled, and files with VI according to defined criteria were selected, and data were collected. Data were analyzed using descriptive and inferential statistics.ResultsMost patients who presented to the hospitals were female (60.7%). The prevalence of VI ranged between 8.1 and 18.2%. VI was more prevalent in females than in males (18.0% vs. 13.7%). Additionally, VI was most prevalent among the elderly (29.1%). The leading causes of VI were diseases of the lens and normal globe diseases. The risk of VI was significantly higher in males (AOR: 1.25; 95% CI: 1.16–1.34), the elderly (AOR: 1.57; 95% CI: 1.40–1.76), and those with diseases of the lens (AOR: 2.17; 95% CI: 1.88–2.51).ConclusionThe burden of VI in Rwanda is expected to increase due to a growing youthful population. Sustained efforts, including improving human resources and addressing the unmet demands of cataract and refractive error, are critical to avert the impending public health challenge.